Probiotics, prebiotics, and the host microbiome: the science of translation. (22nd November 2013) - Petschow, Bryon; Doré, Joël; Hibberd, Patricia; Dinan, Timothy; Reid, Gregor; Blaser, Martin; Cani, Patrice D.; Degnan, Fred H.; Foster, Jane; Gibson, Glenn; Hutton, John; Klaenhammer, Todd R.; et al.
Abstract : Recent advances in our understanding of the community structure and function of the human microbiome have implications for the potential role of probiotics and prebiotics in promoting human health. A group of experts recently met to review the latest advances in microbiota/microbiome research and discuss the implications for development of probiotics and prebiotics, primarily as they relate to effects mediated via the intestine. The goals of the meeting were to share recent advances in research on the microbiota, microbiome, probiotics, and prebiotics, and to discuss these findings in the contexts of regulatory barriers, evolving healthcare environments, and potential effects on a variety of health topics, including the development of obesity and diabetes; the long‐term consequences of exposure to antibiotics early in life to the gastrointestinal (GI) microbiota; lactose intolerance; and the relationship between the GI microbiota and the central nervous system, with implications for depression, cognition, satiety, and mental health for people living in developed and developing countries. This report provides an overview of these discussions.